Pengaruh Stres Kerja, Pengembangan Karir dan Lingkungan Kerja Fisik Terhadap Kepuasan Kerja Karyawan Rumah Sakit Umum Daerah Tabanan - Apriani, Gusti Ayu Putu Dewi; Santosa, Awan (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the effect of job stress, career development, and physical work environment on employee job satisfaction at RSUD Tabanan. The research method used is quantitative with data collection through questionnaires involving 150 respondents. Data analysis was performed using multiple linear regression tests to test the hypothesis. The results showed that job stress has a significant negative effect on employee job satisfaction (significance value 0.019 0.05), while career development has no significant effect on job satisfaction (significance value 0.054 0.05). In contrast, the physical work environment has a significant positive effect on employee job satisfaction (significance value 0.000 0.05). Simultaneously, job stress, career development, and physical work environment have a significant positive effect on employee job satisfaction (F value 25.178 F table 2.666; significance 0.000 0.05). This research implies that good work stress management, improving the quality of the physical work environment, and optimizing career development can increase employee job satisfaction. These results are in line with various theories and previous research, emphasizing the importance of attention to these factors to create a harmonious and productive work atmosphere.